2015
DOI: 10.1139/apnm-2015-0061
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training minimizes catabolic effects induced by sleep deprivation in rats

Abstract: Sleep deprivation (SD) can induce muscle atrophy. We aimed to investigate the changes underpinning SD-induced muscle atrophy and the impact of this condition on rats that were previously submitted to resistance training (RT). Adult male Wistar EPM-1 rats were randomly allocated into 1 of 5 groups: control, sham, SD (for 96 h), RT, and RT+SD. The major outcomes of this study were muscle fiber cross-sectional area (CSA), anabolic and catabolic hormone profiles, and the abundance of select proteins involved in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
3
40
1
Order By: Relevance
“…We were surprised to find a main effect of Bmal1 overexpression (in skeletal muscle) on insulin sensitivity of the skeletal muscle; loss of Bmal1/BMAL1 function and sleep deprivation (NREM and REM) for an extensive duration (96 hours) both compromise insulin sensitivity [6, 7, 8, 27, 28]. No study in rodent models has yet to report a compromise in insulin sensitivity with short durations of sleep deprivation (6 hours), but 12 hours of sleep fragmentation can also compromise insulin sensitivity [29].…”
Section: Discussionmentioning
confidence: 99%
“…We were surprised to find a main effect of Bmal1 overexpression (in skeletal muscle) on insulin sensitivity of the skeletal muscle; loss of Bmal1/BMAL1 function and sleep deprivation (NREM and REM) for an extensive duration (96 hours) both compromise insulin sensitivity [6, 7, 8, 27, 28]. No study in rodent models has yet to report a compromise in insulin sensitivity with short durations of sleep deprivation (6 hours), but 12 hours of sleep fragmentation can also compromise insulin sensitivity [29].…”
Section: Discussionmentioning
confidence: 99%
“…During the training sessions, the animals were placed at the bottom of the ladder to climb the stairs 4–8 times while carrying a load, with 60-second intervals between the series. Animals took 8 to 12 steps to climb from the base to the top of the ladder [28]. …”
Section: Methodsmentioning
confidence: 99%
“…The sessions were conducted five times per week (Monday to Friday), and the Monday training session was replaced by the maximum load test to readjust the load. To avoid overtraining due to the high loads, prophylactic rest was introduced on Wednesday of weeks 6, 7, and 8 [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Sleep-deprivation induced muscle atrophy could be partially restored by a 96-h recovery period [37]. Work from the same group confirmed that a decrease in average muscle fibre CSA induced by sleep-deprivation was specific to glycolytic and mixed muscles and that 96 h of paradoxical sleep deprivation significantly reduced fat deposition in all types of muscle, possibly as a direct consequence of a negative energy balance [39]. Rats subjected to sleep deprivation for 18 h per day demonstrated an increase in the Mhc1 gene and protein expression (a protein that is characteristic of slow-twitch fibres) and a decrease in the Mhc2 gene and protein expression (a protein that is characteristic of fast-twitch fibres) in the masseter muscle after 7 and 14 days; values that returned to baseline levels after 21 days of sleep deprivation [40].…”
Section: A Model For Shiftwork and Skeletal Muscle Healthmentioning
confidence: 99%
“…There are, however, some allied findings in rodents to prompt further investigation into this countermeasure. Monico-Netto et al [39] tested rats’ responses to 96 h of sleep deprivation, eight-week resistance training, and 96 h sleep deprivation following the eight-week resistance training protocol. Resistance training alone increased muscle mass and CSA, while sleep deprivation alone significantly reduced muscle mass and CSA.…”
Section: Potential Countermeasures To Preserve Skeletal Muscle Heamentioning
confidence: 99%